Two new gonad-infecting Philometra species (Nematoda: Philometridae) from the marine fish Lutjanus vitta (Perciformes: Lutjanidae) off New Caledonia - Moravec, Frantisek; Justine, Jean-Lou (Folia parasitologica, 2011)
Two new gonad-infecting species of Philometra Costa, 1845 (Philometridae), P. brevicollis sp. n. and P. mira sp. n., are described from the ovary of the brownstripe red snapper, Lutjanus vitta (Quoy et Gaimard) (Lutjanidae, Perciformes), from the South Pacific Ocean off the coast of New Caledonia. Based on light and scanning electron microscopy examination, these new nematodes are compared with all other gonad-infecting species of Philometra. The former species (males and mature and gravid females available) mainly differs from its congeners in the length of males (5.39-5.92 mm), equally long spicules (279-312 microm), and the gubernaculum (151-168 microm), in that the distal end of the gubernaculum bears dorsolateral transverse lamella-like structures, and in the structure of the male caudal end. The latter species (only males available) is characterized by the length of males (3.47-3.66 mm), equally long spicules (96-105 microm), and the gubernaculum (78-84 microm), the absence of a dorsal reflected barb or lamella-like structures on the distal end of gubernaculum, and by the structure of the male caudal end. Judging from the occurrence in the host, P. brevicollis is the main philometrid parasitizing the gonads of L. vitta, in which it can reproduce, whereas this fish probably serves as only the paradefinitive host for P. mira. Both P. brevicollis and P. mira are the first nominal species of Philometra described from fishes of the family Lutjanidae.
Keywords: mořská voda; Dracunculoidea; Perciformes; Male; Fish Diseases; Gonads; New Caledonia; mužské pohlaví; Nová Kaledonie; Spirurida Infections; Animals; ženské pohlaví; Microscopy, Electron, Scanning; zvířata; nemoci ryb; Ovary; infekce hlísticemi řádu Spirurida; Seawater; Female; mikroskopie elektronová rastrovací; ovarium; gonády